2019
DOI: 10.1016/j.ebcr.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Continuous ictal discharges with high frequency oscillations confined to the non-sclerotic hippocampus in an epileptic patient with radiation-induced cavernoma in the lateral temporal lobe

Abstract: Intraoperative electrocorticography recording is recommended for treating cavernoma-related epilepsy. However, interictal paroxysmal epileptiform activity is generally able to be recorded, but is not always identical to the epileptogenic zone.We surgically treated a 15-year-old girl with drug-resistant epilepsy associated with radiation-induced cavernoma in the right lateral temporal lobe. Electrocorticography revealed paroxysmal activities in the cortex around the cavernoma. Additionally, continuous subclinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Most studies have reported significantly better outcome of CCM-associated epilepsy when the surrounding hemosiderin rim and gliosis were removed [1,2,5,[30][31][32][33][34][35][36][37]. However, there is also some debate on the lesions and the outcomes of epilepsy [35,[38][39][40], and the duration of epilepsy is associated with multiple underlying factors (e.g., white matter volume loss or asymmetrical brain morphologic changes) [41][42][43]. To be sure, the histopathological changes in CCM surrounding or remote tissue definitely play a significant role in the generation of seizures [1,30,32,38,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have reported significantly better outcome of CCM-associated epilepsy when the surrounding hemosiderin rim and gliosis were removed [1,2,5,[30][31][32][33][34][35][36][37]. However, there is also some debate on the lesions and the outcomes of epilepsy [35,[38][39][40], and the duration of epilepsy is associated with multiple underlying factors (e.g., white matter volume loss or asymmetrical brain morphologic changes) [41][42][43]. To be sure, the histopathological changes in CCM surrounding or remote tissue definitely play a significant role in the generation of seizures [1,30,32,38,44].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, although qMPM has the potential to assist clinicians for resection, microhemorrhage is not the only predictor that induces epilepsy. It is currently difficult to detect all epileptogenic zone using label-free optical imaging [33,38,40], because some remote epileptic foci and eloquent cortex need to be identified in combination with functional techniques, such as intraoperative electrocorticography (iECoG) or intraoperative MRI (iMRI) [33,39]. More importantly, if the hemosiderinrelated lesion is involving or closer to eloquent regions, removal of hemosiderin is not recommended in order to prevent neurological deficits, even when epileptogenic foci have been identified by iECoG [31,33].…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the varying definitions of hemorrhage that investigators have used, either radiologically based or clinically based [ 1 , 17 , 29 ], the annual rates of spontaneous RICM bleeding vary from 4 to 23% [ 37 ] in children, which is much higher than spontaneous rates of 0.25%–1% per person-year in adults [ 36 ]. Indeed, hemorrhage was reported in 21% of children either clinically, on imaging, or both during a mean follow-up of 7.4 years (range 1–10.2) [ 10 , 22 , 25 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…When facing a child with recurrent hemorrhage or progressive neurological deterioration with focal neurological deficit in presence of a sufficiently low risk-to-benefit ratio, microsurgery is widely accepted as superior to conservative treatment [ 22 ]. Children suffering from drug-resistant epilepsy, often associated with RICM in the temporal lobe, can benefit from surgery leading to a seizure free and even an anti-seizure treatment free outlook [ 25 ]. Asymptomatic growth and radiological progression suggesting an aggressive behavior are other criteria in favor of surgical removal of an RICM [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…These fast-wave activities were not recorded on EEG, probably due to the smearing effect. [ 5 ] Although these beta and gamma activities could not be categorized as high-frequency oscillations,[ 7 ] as fast oscillations, this finding might indicate that the area was epileptogenic. In fact, no paroxysmal activities were recorded on postoperative EEG, while no significant change in her consciousness level was noted.…”
Section: Discussionmentioning
confidence: 99%